Emergency registrars' and physicians' perceptions and preparedness to respond to the health impacts of climate change: a survey study - Theron, Elzarie (Department of Environmental and Geographical Science, 2025)
Climate change has many significant impacts on health. These impacts occur on top of existing conditions, which places a disproportionate burden on those who are already vulnerable. Emergency healthcare, which is responsible for all acute and urgent aspects of illness and injury, often serves as the first point of contact in the health system for patients who have been affected by climate change. However, it is expected that many emergency medicine specialists are not well versed on the health impacts of climate change, making it essential to assess their current perception of and preparedness to address these impacts in clinical practice. To create an understanding of emergency medicine registrars' and physicians' perceptions about climate change and health, climate-related health education, and self-perceived preparedness to respond to these impacts, this study followed a survey design, using an online questionnaire to collect data. Data were collected from emergency medicine registrars' and physicians' who are currently working in South Africa. The data were first analysed descriptively, and Mann-Whitney U tests were conducted to explore differences amongst sub-groups. Results indicated that most (80%, n = 16) participants recognised the health impacts of climate change and felt that it would impact their own and their patients' health. None of the participants however received any formal training on the topic and only 3 (15%) participants indicated that they probably have enough information to prepare for the health impacts of climate change. Exploratory analysis indicated that the extent to which participants agreed with the statement that climate change will affect their personal health scores was statistically significantly higher for those who identified as women than for participants who identified as men (p = .024). There is a need for better integration of climate-related health education into medical curricula to prepare emergency medicine specialists in response to the health impacts of climate change. Key Terms: emergency medicine, emergency healthcare professional, climate-related health impacts, climate-related health education, medical curriculum, emergency healthcare preparedness, gender differences.